(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Micromorphology and anatomy of six Onosma L. species, viz. O. argentata Hub.-Mor., O. neglecta Riedl, O. proballanthera Rech. f., O. rechingeri Riedl, O. sericea Willd. and O. stenoloba Hausskn. ex Riedl from Turky were investigated. Stem anatomy revealed that cuticle layer ranged from 0.6 µm in O. argentata to 1.7 µm in O. proballanthera. Parenchymatous cells of O. neglecta and O. stenoloba possessed more intense starch than the other species studied. In leaf anatomy, the longest palisade parenchyma was found in O. neglecta, while the smallest was noted in O. argentata. Mesophyll structure of O. argentata, O. sericea and O. rechingeri was equifacial (isobilateral), while O. neglecta, O. proballanthera and O. stenoloba presented bifacial (dorsiventral) structure. Rugose nutlet ornamentation was observed in O. argentata, O. neglecta and O. sericea, whereas reticulate type was found in O. proballanthera, O. rechingeri and O. stenoloba. Onosma stenoloba could easily be distinguished from other species by its aesterotrichous indumentum, and in contrary, other species possessed haplotrichous type of indumentum. Micromorphological features of nutlet surface, anatomical features of epidermal surface (trichomes and stomata), and lamina mesophyll structure (dorsiventral and isobilateral) could be useful in solving taxonomic problem of the genus.